THE IMPACT OF SCHOOL LITERACY MOVEMENT (GSL) ON THE LITERACY ABILITY OF THE FIFTH GRADERS AT SD NEGERI GUNUNG SARI, RAPPOCINI DISTRICT, MAKASSAR CITY - Syawaluddin, Ahmad; haedah, Nur (International Journal of Elementary Education, 2017)
This researchÂ  was aimed at knowing the impact ofÂ  (GLS) on the studentsâ literacy ability of the fifth graders atÂ  SD Negeri Gunung Sari I,Â Â  Rappocini district,Â  Makassar city in the school year 2016/2017. The research approach used a quantitative approach with Pre-experimental Research design. The sample was selectedÂ  with purposive sampling by choosing class V as experiment class with the total number ofÂ  66 students andÂ  those who were present wereÂ  50 students. The techniques of data collection used in this research wereÂ  test and documentation. The data collected from the literacy ability test result were then analyzed using descriptive statistical analysis and inferential statistical analysisÂ  usingÂ  sample t-test ofÂ  Wilcoxon Test by using the test of two sides (two tailed test).Â  To test the normality of the data distribution,Â  Kolmogrov-Smirnov Normality Test was used with Asymp Sig. (2-Tailed)Â  of 0.002 for pretest data and 0.003 for posttest data. Literacy ability on initial test (pretest) was in very satisfactory category with the mean of 83.99 and the literacy ability in the final test (posttest) was in very satisfactory category with the mean of 90.23. Hypothesis testing was done by usingÂ  Wilcoxon Test Asymp Sig. (2-tailed) the value was 0.00 < 0.05. The conclusion of research based on the result of analysis showedÂ  that there is an impactÂ  of school literacy movement (GLS) on studentsâ literacy ability of fifth graders ofÂ  SD Negeri Gunung Sari I inÂ  RappociniÂ  disctrict,Â  Makassar city